2005
DOI: 10.3928/01913913-20050101-02
|View full text |Cite
|
Sign up to set email alerts
|

Vitrectomy for Dense Vitreous Hemorrhage in Infancy

Abstract: Purpose: To report clinical data, including etiology and visual outcome, in newborns requiring vitrectomy for dense vitreous hemorrhage. Methods: In this retrospective case series, we surveyed subscribers to the American Association for Pediatric Ophthalmology and Strabismus ListServe regarding patients under their care. Results: A total of 28 eyes of 21 patients were included. Most common etiologies were th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 9 publications
1
6
0
Order By: Relevance
“…In infants, idiopathic causes were more compared to children over 1 year of age. [14] This was also noted by Al Harkan et al [30] This also corroborates with a previous study[28] which stated that in many cases, the exact cause was unknown in infants. Sudhalkar et al [33] state that this has more to do with the practical difficulty in eliciting appropriate history and clinical signs and symptoms in young children.…”
Section: Methodssupporting
confidence: 90%
See 1 more Smart Citation
“…In infants, idiopathic causes were more compared to children over 1 year of age. [14] This was also noted by Al Harkan et al [30] This also corroborates with a previous study[28] which stated that in many cases, the exact cause was unknown in infants. Sudhalkar et al [33] state that this has more to do with the practical difficulty in eliciting appropriate history and clinical signs and symptoms in young children.…”
Section: Methodssupporting
confidence: 90%
“…[7] On reviewing the literature, different causes of pediatric vitreous hemorrhage have been published, most of these either being case reports or case series that have focused on different modalities of treatment. [8910111213141516171819202122232425262728] There is lack of evidence comprehensively reviewing the etiologies or giving definite guidelines regarding the management of vitreous hemorrhage in the pediatric age group. We attempt to present a narrative review on the demographic profile, etiology, clinical manifestations, treatment modalities, and outcomes of vitreous hemorrhage in children from the major studies available in literature till date.…”
mentioning
confidence: 99%
“…Other etiologies associated with vitreous hemorrhages in pediatric age group are separated in traumatic and nontraumatic causes. Nontraumatic causes are, in order of frequency, retinoblastoma, Terson’s syndrome, persistent fetal vasculature, idiopathic, regressed retinopathy of prematurity, familial exudative vitreoretinopathy, intermediate uveitis, associated with lymphoblastic leukemia, retinitis pigmentosa, familial retinal artery macroaneuvrysm, nanophtalmos, neonatal meningitis, panuveitis (brucellosis), Stickler diseases with rhegmatogenous retinal detachment (RRD), arteriovenous malformation, Coats disease and Marfan syndrome with RRD [ 21 ]. Coagulation disorders could also be implied, including leukemia, haemophilia, Von Willebrand disease and Protein C deficiency [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…In children, however, vitreous hemorrhage is uncommon, and as a result, it is not studied as well as in the adult age group and little is known about it. On literature review, different causes have been published, but most of these publications are either case reports or a small series describing particular group of patients or different modalities of treatment [ 6 26 ]. To the best of our knowledge, there are only two studies that investigated vitreous hemorrhage as a separate entity in children in English literature and these studies showed different causes than that published in adults [ 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%